(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The majority of Tikrit university students do not use linking in their speech. The total number of their correct replies (136, 23%) islower than that of the incorrect ones (464, 77%). This verifies the first hypothesis of the study.They encounter more difficulty at the spoken performance. Thus, thetotal number of their correct responses of the written performance (340, 28%) is more than that of the spoken one (232, 26%). This confirms the second hypothesis. They encounter more difficulty at the production level. For this reason, the total number of their incorrect responses at the production level (955, 80%) is higher than that of the recognition one (573, 64%). This confirms the third hypothesis